Validating Neuro-Computational Models of Neurological and Psychiatric Disorders - Bhattacharya, Basabdatta Sen; Chowdhury, Fahmida N. (Springer Series in Computational Neuroscience, 2015)
This book is a collection of articles by leading researchers working at the cutting edge of neuro-computational modelling of neurological and psychiatric disorders. Each article contains model validation techniques used in the context of the specific problem being studied. Validation is essential for neuro-inspired computational models to become useful tools in the understanding and treatment of disease conditions. Currently, the immense diversity in neuro-computational modelling approaches for investigating brain diseases has created the need for a structured and coordinated approach to benchmark and standardise validation methods and techniques in this field  of research. This book serves as a step towards a systematic approach to validation of neuro-computational models used for studying brain diseases, and should be useful for all neuro-computational modellers.